1990
DOI: 10.1083/jcb.110.5.1673
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl-3,4-dihydroxybenzoate inhibits myoblast differentiation: evidence for an essential role of collagen.

Abstract: Abstract. To study the role of (pro)collagen synthesis in the differentiation of rat L6 skeletal myoblasts, a specific inhibitor of collagen synthesis, ethyl-3,4-dihydroxybenzoate (DHB), was utilized. It is shown that DHB reversibly inhibits both morphological and biochemical differentiation of myoblasts, if it is added to the culture medium before the cell alignment stage. The inhibition is alleviated partially by ascorbate, which along with ot-ketoglutarate serves as cofactor for the enzyme, prolyl hydroxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 41 publications
4
50
0
Order By: Relevance
“…In particular, the synthesis of collagen and other extracellular matrix proteins has shown to be essential for myogenic differentiation (23). Here we provide the initial evidence that DDR1 may play an important role in the differentiation of cultured mouse skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 56%
“…In particular, the synthesis of collagen and other extracellular matrix proteins has shown to be essential for myogenic differentiation (23). Here we provide the initial evidence that DDR1 may play an important role in the differentiation of cultured mouse skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 56%
“…Inhibition of collagen synthesis reduced MRF expression and prevented myogenic differentiation in a manner that could be reversed with exogenous collagen in Matrigel (51,52). Similarly, the loss of proteoglycans in the extracellular matrix by synthesis inhibitors inhibited differentiation and could be rescued by exogenous extracellular matrix administration (53)(54)(55).…”
Section: Discussionmentioning
confidence: 91%
“…It is accepted that cell-matrix adhesion plays an important role in regulating differentiation. Studies have shown that inhibition of extracellular matrix synthesis [Nandan et al, 1990;Saitoh et al, 1992] as well as blockage of integrin function [Menko and Boettiger, 1987] inhibits the differentiation of myoblasts. Moreover, myoblasts in suspension fail to differentiate in the absence of substrate adhesion [Milasincic et al, 1996].…”
Section: Discussionmentioning
confidence: 99%